PEMANFAATAN PANTAI AYAH SEBAGAI SUMBER BELAJAR GEOGRAFI KELAS X MATERI POKOK HIDROSFER SMA NEGERI SUMPIUH TAHUN AJARAN 2014/2015 - Alin Anggini (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2016)
This study aims to determine the implementation of learning Geography, to analyze learning outcomes ofGeography, and to discover the advantages as well as obstacle factors in implementation of learningGeography of class X subject matter Hydrosphere, which used “Pantai Ayah” as learning source. Thisresearch methodology used descriptive quantitative. Population of this research were all student of class Xin Sumpiuh Senior High School. Sampling technique were using random sampling. Data collected throughtests, questionnaires, observation, documentation, and interview. Results of this research showed thatlearning implementation was great with the preparatory percentage stage 100%, the implementation 83,3%,and the follow up 91,6%. It showed 24 students got mark over minimum rate criterion and 6 students gotunder minimum rate criterion. The advantages of this learning were increased knowledge of outdoor studymethod, interesting learning increased creativity, increased learn interest, enthusiastic attitude as well asgood infrastructure provision. Obstacle factors were cost, time, distance, physical condition, and security.